Prediction of Prognostic Factors in the Survival of Non-small-cell Lung Cancer Patients with Multiple Brain Metastases - Özlem Mermut; Berrin İnanç; Aytül Hande Yardımcı (İstanbul Medical Journal, 2021)

(untitled)
Introduction:We aimed to investigate the factors affecting survival in non-small-cell lung cancer (NSCLC) patients with multiple brain metastases.Methods:One hundred thirty patients who were diagnosed with NSCLC at the time of presentation or during disease follow-up were evaluated at University of Health Sciences Turkey, İstanbul Training and Research Hospital, Clinic of Radiation Oncology between 2012 and 2017.Results:In univariate analysis, significant effects of age >60 (p=0.006), stage 4 at the time of diagnosis (p<0.001), Karnofsky Performance score (KPS) <70 (p<0.001), extracranial metastasis presentation (p=0.014), uncontrolled primary tumor (p=0.002), headache (p=0.037), and recursive partitioning analysis (RPA) Class III (p<0.001) were observed in predicting early mortality. In multivariate Cox regression analysis, stage 3 at the time of diagnosis [hazard ratio (HR): 0.419, 95% confidence interval (CI): 0.217-0.809, p=0.010], KPS ≥70 (HR: 14.515, 95% CI: 5.470-38.519, p<0.001), and RPA Class I-II (HR: 0.192, 95% CI: 0.102-0.362, p<0.001) had a positive effect on overall survival.Conclusion:Predicting prognostic factors when making whole- brain radiotherapy decisions in NSCLC patients with multiple brain metastases will help in treating such patients appropriately. In multiple brain metastases with NSCLC patients, stage 3 at the time of diagnosis, KPS ≥70, and RPA Class I-II have a positive effect on overall survival.